(untitled) (Al-Mansour Journal, 2023)
In this paper we discuss the use of COCOMO II (Constructive Cost Model ) to estimate the cost of software engineering . The COCOMO II which allow us estimate the cost, effort and scheduling when planning new software development . We use the effort equation guidance to find the number of person / months which is needed to complete the project and duration equation to specified the numbers of months which is needed to complete this project. This paper present how implemented COCOMO II model equation about the same data in different language we choose C and OOP(C++),we make the analysis of these two program and we conclude that relation between effort and duration was forward relation, we mean that when effort increasing duration will increasing in the author side.